2021
DOI: 10.30935/ejimed/11439
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Pedagogy: Interrogating Ways of Promoting Deeper Learning in Higher Education

Abstract: Teaching and learning in higher education should shift from surface learning to deeper learning. Deeper learning provides opportunities for students to achieve high learning outcomes. However, there is a dearth of information on the utilization of deeper learning in higher education. Deeper learning demands educators to employ pedagogy that enhances the acquisition of higher-order skills. Through deeper learning, students develop critical skills that are necessary for the twenty-first century. Such skills enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Those writing about the topic advocate the need for a dramatic change in the nature, content and process of learning through a form of leadership that focuses on instructional change and innovation. Deeper learning is conceptualised as a set of educational outcomes that equip students to deal with challenges, that include working on problem-solving, content knowledge, critical thinking, communication and collaboration, learning how to learn, transferring knowledge and skills, the use of digital technology and supporting students to become life-long learners Mthethwa-Kunene et al, 2022).…”
Section: Deeper Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Those writing about the topic advocate the need for a dramatic change in the nature, content and process of learning through a form of leadership that focuses on instructional change and innovation. Deeper learning is conceptualised as a set of educational outcomes that equip students to deal with challenges, that include working on problem-solving, content knowledge, critical thinking, communication and collaboration, learning how to learn, transferring knowledge and skills, the use of digital technology and supporting students to become life-long learners Mthethwa-Kunene et al, 2022).…”
Section: Deeper Learningmentioning
confidence: 99%
“…Fullan et al (2019, p. 65) further endorse that deeper learning helps students "make connections to the world, to think critically, work collaboratively, empathize with others, and, most of all, be ready to confront the huge challenges that the world is leaving their generation". An essential aspect of deeper learning, it is proposed, is the transfer of knowledge that results in the ability to transfer what is learned from one environment to another and help to make connections within and between the academic environment to the real world (McGregor, 2020;Mthethwa-Kunene et al, 2022). Zhao (2020, p. 29) explains that such rethinking should focus on the "what, how, and where of learning" and that this should be derived "from the perspectives of the children instead of the curriculum".…”
Section: Deeper Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important instructional strategy, collaborative learning emphasizes learner-centered instruction and has a positive impact on students' learning performance (Chadha, 2019;Molinillo et al, 2018). Such tasks as student presentations, group work, and interactive projects provide students with opportunities for effective communication and meaningful engagement with the learning content (Mthethwa-Kunene et al, 2022). Vázquez-Cano et al (2020) found that college students were more apt at communicating through interactive presentations, as well as at collaborating online through mobile devices.…”
Section: Literature Review Deeper Learningmentioning
confidence: 99%